Discussion of psychiatric comorbidity via a bipolar patient with problematic internet use: case report - Köroğlu, Gültürk; Öztürk, Özgür; Tellioğlu, Nergis; Genç, Yasin; Mırsal, Hasan; Beyazyürek, Mansur (Journal of Dependence, 2006)
As rapidly advancing technology facilitates internet access for many people, behavioral problems emerge and new psychiatric descriptions are needed. The motivation underlying the task to create new diagnostic criteria is to answer the question whether overuse of internet is a unique diagnostic category or is a disorder like paraphilias, pathologic gambling or bipolar disorder. The question arose from the observations that subjects with problematic internet use had a high percentage of comorbid psychiatric disorders. Although there are many reports about problematic internet use, no study on this field has been performed in Turkey. The aim of this article is to discuss the diagnosis of problematic internet use and psychiatric comorbidity of a subject who had internet overuse.